Antecedents of safety behaviour among operators at light rail transit and KL Monorail services in Malaysia - Ruzilawati, Isnin (2017)
Safety behaviour is one of the area concern in reducing incident and accidents in services and non-services industries. This bottom-up approach becomes favourable since the work systems and associated technologies are improved. There are two dimensions of safety behaviours viz safety compliance and safety citizenship behaviours (SCBs). The safety compliance refers to employees’ compliances behaviours to organization safety requirements accordance to organization and related regulatory bodies. Meanwhile, SCBs refers to employees’ extra-role behaviours in achieving higher safety standard in organizational level. By considering individual and leadership factors which are safety knowledge, safety motivation, safety-specific transformational leadership (SSTL) and safety consciousness, this determines the level of safety behaviour among operators at LRT and KL Monorail service. 326 sets of questionnaire survey were distributed at rail maintenance and rail operation departments of LRT and KL Monorail. According to the survey, 98 data were collected by presenting 30 percent of respondents’ rate. Data was analysed by using Statistical Package for the Social Science (SPSS) version 23.0. The results of the study revealed, that only three variables exerted significant correlation with safety behaviour viz safety knowledge, safety motivation and SSTL whereby the correlation between safety consciousness and safety behaviours is not significant. Contributions, limitations, and implications of the study are discussed.